Challenges and advantages of recycling wrought aluminium alloys from lower grades of metallurgically clean scrap - Kevorkijan, Varužan (Materiali in tehnologije, 2013)
In the recycling of wrought aluminium alloys from lower grades of scrap (metallurgically clean but highly contaminated with non-metallic impurities) the following two tasks were identified as the most demanding: (i) achieving the required final chemical composition of an alloy with a minimal addition of primary aluminium and alloying elements; and (ii) keeping the level of impurities (inclusions, hydrogen, trace elements and alkali metals) in the molten metal below the critical level. Because of the lack of chemically based refining processes for reducing the concentration of alloying and trace elements in the molten aluminium, once the concentrations of these constituents in the melt exceed the corresponding concentration limits, the only practical solution for their reduction would be an appropriate dilution with primary metal. To avoid such a costly correction, carefully predicting and ensuring the chemical composition of the batch in the pre-melting stage of casting should be applied. Fortunately, some of the impurities, like hydrogen and alkali metals, as well as various (mostly exogeneous) inclusions, could be successfully reduced by employing existing refining procedures. In this work, (i) the state-of-the-art technologies, including some emerging technical topics such as the evolution of wrought alloys toward scrap-intensive compositions, monitoring of the content of organics in the incoming scrap and the quality of molten metal achieved by different smelting and refining technologies, and (ii) the relevant economic advantages of the recycling of wrought aluminium alloys from the lower grades of scrap are reported. By analyzing the market prices of various grades of scrap and the total cost of their recycling, the cost of aluminium ingots made from recycled aluminium was modelled as a function of aluminium and the alloying-element content in the incoming scrap. Furthermore, scrap mixtures for producing aluminium wrought alloys of standard quality from lower grades of scrap and with a significant new added value were illustrated.
Keywords: odpadne kovine; aluminijeve zlitine; aluminium alloy; recikliranje; kvaliteta